Melting Behavior Effect of MXene Nanoenhanced Phase Change Material on Energy and Exergy analysis of Double and Triplex Tube Latent Heat Thermal Energy Storage - Srivastava U.; Sahoo R.R. (My University, 2025)
The impacts of melting behavior on the thermal performance of triple tube thermal energy storage (TT-TES) and double tube thermal energy storage (DT-TES) systems employing cetyl alcohol and 3% v/v. MXene nano-enhanced PCM (NEPCM) are compared and numerically evaluated in this work. For both the DT-TES and TT-TES systems, the following were investigated in connection to melting time: system efficiency, discharged energy, heat transfer rate, exergy destruction, entropy generation number, exergetic efficiency, melting fraction, and melting temperature contours. In addition, the effect of Stefan, Rayleigh, and Nusselt numbers on Fourier numbers are compared for the DT-TES and TT-TES systems with MXene NEPCM. MXene-based nano-enhanced PCM melting in TT-TES displayed 6.53% more Stefan number than cetyl alcohol. DT-TES with pure cetyl alcohol phase change material (PCM) consumes 0.4% more energy at 7800 s than MXene NEPCM. Pure melting of MXene-based nano-enhanced PCM in a TT-TES had 4.16% higher storage exergy than cetyl alcohol. The entropy generation number of pure melting of MXene-based nano-enhanced PCM in TT-TES is 7.93% lower than that of cetyl alcohol. Pure melting of MXene-based nano-enhanced PCM in TT-TES reduces storage energy by 1.95% over cetyl alcohol. Pure cetyl alcohol has 76.99% optimal system efficiency at 5400 s melting time and MXene NEPCM 77.04% at 4800 s in DT-TES. The charging temperature for pure cetyl alcohol PCM in TT-TES is 0.7% lower than in DT-TES. Furthermore, pure melting of MXene-based nano-enhanced PCM in a TT-TES has 1.95% lower storage energy than cetyl alcohol. For a given volume of MXene-based nano-enhanced cetyl alcohol PCM, melting occurs more rapidly in a TT-TES system. © 2024 by ASME.